Systemic lupus erythematosus manifestation following COVID-19: a case report - Batool Zamani; Seyed-Masoud Moeini Taba; Mohammad Shayestehpour (Journal of Medical Case Reports, 2021)
Abstract Background Systemic lupus erythematosus (SLE) is a complex and challenging autoimmune disease. Severe acute respiratory syndrome coronavirus 2 (SARS‑CoV‑2) is a novel viral agent that can cause a life-threatening respiratory disorder named coronavirus disease 2019 (COVID‑19). Association between SARS‑CoV‑2 and SLE is not clear. We reported the first case of SLE manifestation following COVID-19. Case presentation A 39-year-old Iranian/Persian man with complaints of fever, scaling on the palms of the hands and feet, lower extremity edema, and ankle swelling was referred to Kashan Rheumatology Clinic in 2020. He was infected with SARS-CoV-2 2 months ago. The patient had proteinuria and was positive for SLE laboratory tests. After one week of treatment with prednisolone (30 mg daily) and hydroxychloroquine, paresthesia, proteinuria, and edema continued. The patient was treated with pulse methylprednisolone (1000 mg for three consecutive days), gabapentin, and vitamin B (300 mg daily), which reduced paresthesia. Conclusions This is the first case of SLE manifestation following COVID-19. SARS-CoV-2 may produce autoantibodies or develop the clinical features of subclinical SLE.